2016
DOI: 10.1038/srep21061
|View full text |Cite
|
Sign up to set email alerts
|

Drug testing and flow cytometry analysis on a large number of uniform sized tumor spheroids using a microfluidic device

Abstract: Three-dimensional (3D) tumor spheroid possesses great potential as an in vitro model to improve predictive capacity for pre-clinical drug testing. In this paper, we combine advantages of flow cytometry and microfluidics to perform drug testing and analysis on a large number (5000) of uniform sized tumor spheroids. The spheroids are formed, cultured, and treated with drugs inside a microfluidic device. The spheroids can then be harvested from the device without tedious operation. Due to the ample cell numbers, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
143
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 171 publications
(158 citation statements)
references
References 35 publications
(45 reference statements)
4
143
0
5
Order By: Relevance
“…19,23 Recently, innovative but sophisticated solutions have taken advantage of new technologies, such as microfluidics, to improve the control of size and composition of MCTS while maintaining high throughput (Table 1). 19,36 To be more representative of tumor complexity, coculture of tumor cells with immune, endothelial cells or fibroblasts helps to better understand a crosstalk between cancer and stromal cells as well as the mechanisms of metastatic invasiveness. 19,33,37 For example, the migration of endothelial cells into MCTS or the formation of vascular networks within spheroids is often used to assess the potential of tumor vascularization.…”
Section: Characteristics Of Mcts Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…19,23 Recently, innovative but sophisticated solutions have taken advantage of new technologies, such as microfluidics, to improve the control of size and composition of MCTS while maintaining high throughput (Table 1). 19,36 To be more representative of tumor complexity, coculture of tumor cells with immune, endothelial cells or fibroblasts helps to better understand a crosstalk between cancer and stromal cells as well as the mechanisms of metastatic invasiveness. 19,33,37 For example, the migration of endothelial cells into MCTS or the formation of vascular networks within spheroids is often used to assess the potential of tumor vascularization.…”
Section: Characteristics Of Mcts Modelmentioning
confidence: 99%
“…19,40,41 Moreover, the development of MCTS-based biosensor devices is becoming widespread. 36,42 Recently, Patra et al demonstrated the advantage to couple microfluidics with flow cytometry for the rapid production and viability analysis of a great number of MCTS with well-defined size, which were submitted to different drugs and their combination. 36 Drug screening typically involves several steps.…”
mentioning
confidence: 99%
“…Microwells [8,25,[87][88][89] and U-shaped microstructures [21,64,[90][91][92][93] have been designed for spheroid formation and culture in microfluidic platforms. These structures facilitate short-term [23,94], controllable and uniform diameter [22,95] and compact spheroid generation [32,92].…”
Section: Microfluidic Methods For Spheroid Culturementioning
confidence: 99%
“…Few minutes are needed that cells deposit on the bottom of the microwells and the microchannel ( Figure 4B). The cells that did not trap in the microwells are pushed out of the chip before the cells make aggregations and clog microchannels [8,24,103] (Figure 4C). Next, the cells begin aggregation and form spheroids ( Figure 4D) and are culture for drug screening ( Figure 4E).…”
Section: Microfluidic Methods For Spheroid Culturementioning
confidence: 99%
See 1 more Smart Citation